HUBUNGAN TIPE KEPRIBADIAN DENGAN PILIHAN KARIR PESERTA DIDIK KELAS XI MAN 1 PONTIANAK - Nurazizah, Nurazizah; Asrori, M.; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCareer choices is one of the most important decision-making processes in an individual's life. The decisions he makes will have an impact on what will pass in his life. It is important to establish a linkage or fit between individual personality types and certain career choices in which, in Holland's view, career selection and adjustment is a description of one's personality. Holland's theory also formulates personality types into six, among others, realistic, intellectual, social, conventional, enterprising, and artistic. The purpose of this research is to get information and describe about the relationship of personality type with career choice of students of class XI MAN 1 Pontianak. The method used is descriptive method. Based on the results of this study indicate that the most dominant personality type of students class XI MAN 1 Pontianak is the conventional personality type achieved the score of 80% with the category "Very High." While career choices are the most dominant career choice in students XI MAN 1 Pontianak is the choice of realistic and social careers reached 77% with the category "High." Based on the results of research by using correlation method Pearson level, obtained correlation coefficient correlation rs = 0.881. This indicates a correlation. So it can be concluded that in this study "There is a correlation between personality types and career choices of XI brade students at MAN 1 Pontianak." Keywords: Personality Type, Career Choices